On the need for methodocentrism in music teachers training system - Jankowski, Wojciech Benedykt (Interdisciplinary Studies in Musicology, 2018)
The main idea of this paper, dedicated to Professor Andrzej Rakowski, is to emphasize that the pedagogy concentrated around the school curriculum and school subjects (eg. Music) has become more and more outdated. More useful seems to be a pedagogy oriented towards the so-called Great Author Concepts (Methods) of Music Education, eg. Dalcroze, Orff, Kodaly, Gordon and others. The author of the report provides a justification for his opinion, as well as specifying its purpose and the conditions under which it was formed. Primarily, the proposed approach involves combining the universality of the Methods with the individual preferences of both the teachers (representing the Method) and the students, providing the possibility of choice. The author sees the special value of that point of view in the integrative character of these Methods - combining an active and creative approach to music with the students’ perceptual and intellectual development. The report also highlights the requirement for a high level of teacher competence in the use of all the methods. Taking into the consideration all of the above (discussed in more detail in this report), the author puts forward a proposal for the reform of the system of training music teachers. According to the author, the system ought to be founded on the Methods (e.g. on one of them, particularly where the Concept/Method is already well developed).